MAGNITUDE OF DEVELOPMENTAL DELAYS AMONG TRIBAL CHILDREN AND EFFECT OF EARLY INTERVENTION - M. SARADA DEVI, M. DEEPA and (The Journal of Research, PJTSAU, 2019)
Infancy and early childhood are the paramount for prevention and amelioration of problems that could potentially cause developmental difficulties and affect brain development across the lifespan. Developmental delay refers to a child not achieving ‘developmental milestones’ at the right age. These ‘milestones’ refer to sets of functional skills or agespecific tasks that most children can do in a certain age-range. Delays may be in physical ability or cognitive ability. Identifying such lags and intervening at the earliest can prevent disability to a large extent in children. India has 2.04 million disabled children aged between 0 and 6 years. Around 71 percent of them i.e., 1.45 million are in rural areas, as per the 2011 Census. Tribals are one of the most vulnerable groups in India.